2016
DOI: 10.1080/17453674.2016.1256937
|View full text |Cite
|
Sign up to set email alerts
|

Bone cement product and failure in total knee arthroplasty

Abstract: Background and purpose — The bone cement market for total knee arthroplasty (TKA) in Norway has been dominated by a few products and distributors. Palacos with gentamicin had a market share exceeding 90% before 2005, but it was then withdrawn from the market and replaced by new slightly altered products. We have compared the survival of TKAs fixated with Palacos with gentamicin with the survival of TKAs fixated with the bone cements that took over the market.Patients and methods — Using data from the Norwegian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…It will be of great importance to determine whether the PMMA-TBB material can avoid in vivo pathologic changes by its polymerization temperature in a future study. In particular, antibiotics containing bone cements have become common recently, and their effectiveness is known to be susceptible to the temperature of the bone cement [2,59].…”
Section: Discussionmentioning
confidence: 99%
“…It will be of great importance to determine whether the PMMA-TBB material can avoid in vivo pathologic changes by its polymerization temperature in a future study. In particular, antibiotics containing bone cements have become common recently, and their effectiveness is known to be susceptible to the temperature of the bone cement [2,59].…”
Section: Discussionmentioning
confidence: 99%
“…Refobacin Bone Cement R has been used for several years at our hospital, and several studies including registry and RSA studies suggest that this cement gives good fixation and long-term survivorship. 36 - 38 The GMK Sphere has a shorter but wider wing of the keel than for instance the NexGen CR (Zimmer Biomet) and the Triathlon CR (Stryker, USA), both known for their excellent survivorship. 39 In theory, this could increase the rotation of the implant.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis performed by the CDC guidelines group, concluded that there were “ uncertain trade-offs between the benefits and harms ” and no recommendation was provided (Berrios-Torres et al, 2017). Importantly, the most common antibiotics incorporated into cement are aminoglycoside antibiotics, whereas only one trial has examined gentamicin (Josefsson and Kolmert, 1993), all other randomized controlled trials examined the incorporation of cefuroxime into cement (Birkeland et al, 2017). Despite this, the use of antibiotic-loaded cement is routinely performed in many centers (International Consensus Meeting on Periprosthetic Joint Infection, 2013).…”
Section: Preventionmentioning
confidence: 99%